2021
DOI: 10.1002/mc.23303
|View full text |Cite
|
Sign up to set email alerts
|

YAP/TEAD4‐induced KIF4A contributes to the progression and worse prognosis of esophageal squamous cell carcinoma

Abstract: Aberrant expression of kinesin family member 4A (KIF4A), which is associated with tumor progression, has been reported in several types of cancer. However, its expression and the underlying molecular mechanisms regulating the transcription of KIF4A in esophageal squamous cell carcinoma (ESCC) remain largely unclear. Here, we found that high KIF4A expression was positively correlated with tumor stage and poor prognosis in ESCC patients. KIF4A silencing significantly inhibited the growth and migration of ESCC ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…TEAD4 plays an oncogenic role in many cancers including gastric cancer, hepatocellular carcinoma, lung adenocarcinoma and head neck squamous cell carcinoma by increasing cancer cell proliferation, migration and epithelial-mesenchymal transition (EMT) [46][47][48]. For example, Li et al reported that YAP/TEAD4 interaction mediates transcriptional activity of KIF4A promoter by binding KIF4A promoter, which will promote cell growth of esophageal squamous cell carcinoma (ESCC) cells [49]. More importantly, DKK1 (dickkopf-1) increases ASMC proliferation and migration by upregulating ubiquitin-like containing PHD and RING finger domains 1 (UHRF1) expression through YAP-TEAD1/4 pathway [50].…”
Section: Discussionmentioning
confidence: 99%
“…TEAD4 plays an oncogenic role in many cancers including gastric cancer, hepatocellular carcinoma, lung adenocarcinoma and head neck squamous cell carcinoma by increasing cancer cell proliferation, migration and epithelial-mesenchymal transition (EMT) [46][47][48]. For example, Li et al reported that YAP/TEAD4 interaction mediates transcriptional activity of KIF4A promoter by binding KIF4A promoter, which will promote cell growth of esophageal squamous cell carcinoma (ESCC) cells [49]. More importantly, DKK1 (dickkopf-1) increases ASMC proliferation and migration by upregulating ubiquitin-like containing PHD and RING finger domains 1 (UHRF1) expression through YAP-TEAD1/4 pathway [50].…”
Section: Discussionmentioning
confidence: 99%
“…MXD3 has been shown to predict poor prognosis in clear cell renal cell carcinoma ( Zhang et al, 2021 ) and hepatocellular carcinoma ( Xu et al, 2019 ), as well as having been indicated as a new molecular targeted site to treat neuroblastoma ( Yoshida et al, 2020 ). PLK1 ( Iliaki et al, 2021 ), EPHK10 , and KIF4A also play important roles as prognostic indicators or as targeted therapy sites for the progression of multiple tumors, such as pancreatic cancer ( Zhu et al, 2021 ), esophageal squamous cell carcinoma ( Li et al, 2021 ), bladder cancer ( Zheng et al, 2021 ), and lung cancer ( Kirienko et al, 2021 ). Furthermore, EPHA10 has already been approved as a potential therapeutic target of prostate cancer ( Nagano et al, 2014 ), and high EPHA10 expression correlated with lymph node metastasis of breast cancer ( Nagano et al, 2013 )—the type of malignant behavior that usually predicts a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, among the various molecules that regulate EMT, TEAD transcription factors and their transcriptional co-activator YAP, a powerful oncoprotein, are crucial regulators that control the expression of genes critical for EMT and metastasis ( 27 , 35 , 36 ). Additionally, substantial evidences have revealed that the YAP-TEADs functional module plays a positive role in the progression of ESCC ( 37 , 38 ). On the other hand, YAP was regarded as a candidate oncogene in ESCC decades ago ( 20 ).…”
Section: Discussionmentioning
confidence: 99%